Building the First Statewide Quality Improvement Collaborative, the CPQCC: A Historic Perspective - Jeffrey B. Gould (MDPI AG, 2020)
The California Perinatal Quality Improvement Collaborative (CPQCC), founded in 1997, was the country's first statewide perinatal quality improvement collaborative. Our goal was to improve the quality and outcomes of perinatal healthcare in California by developing a collaborative network of public and private obstetric and neonatal providers, insurers, public health professionals, and business groups to support a system for benchmarking and performance improvement activities for perinatal care. In this presentation, we describe how viewing the CPQCC as a complex value-driven organization, committed to identifying and addressing the needs of both its stakeholder partners and neonatal intensive care unit (NICU) members, has shaped the course of its development.